Uncertain Discrete-Time Systems with Delayed State: Robust Stabilization with Performance Specification via LMI Formulations - Leite, Valter J. S.; Castro, Michelle F. F.; Caldeira, André F.; Miranda, Márcio F.; Gonçalves, Eduardo N. (IntechOpen, 2011)
None